A STATISTICAL INVESTIGATION OF THE EFFECTS OF SIZE ON INCOME SMOOTHING BEHAVIOUR OF COMPANIES LISTED IN NSE - Bora, Dr. Jutimala (The journal of contemporary issues in business and government, 2022)
Objectives. :Financial reporting is a process of communicating financial information of the companies to different stakeholders. Financial reporting process of companies has been constantly facing the problem of satisfying different stakeholders with diverse needs and desires. Satisfaction of one’s needs leads to the dissatisfaction of others. In order to satisfy all kind kinds of stakeholders, there is a need to maintain a balance between the two extreme points i.e. higher profit and lower profit. Due to various reasons like increasing level of competition and loopholes in the accounting standards, Companies are using different techniques of Creative Accounting to manipulate the Accounts.There are various forms of Creative Accounting. Income Smoothing is one type of Creative Accounting. In this study, it has been tried to determine theexistence of Income Smoothing in the Companies listed in Indiaand theassociation between the size of the companies and the Income Smoothing practices of Companies has also been studied. Methods: Eckel Index has been calculated to detect the existence of Income Smoothing practices of Companies. Inferential Statistics like Chi Square Test and Binary Logistic Regression Model has been conducted. Findings: Results show that Income Smoothing is prevalent among the Companies listed in India and Size of the Companies has been found as a significant factor affecting Income Smoothing Behaviour.